PTFE Distribution in High-Temperature PEM Electrodes and Its Effect on the Cell Performance - Mack, Florian; Morawietz, Tobias; Hiesgen, Renate; Kramer, Dominik; Zeis, Roswitha (ECS Transactions, 2013)
A conventional high-temperature polymer electrolyte membrane (HT-PEM) fuel cell electrode primarily consists of carbon-supported platinum catalyst and nonconductive binder PTFE. Morphology and topography of the electrodes were determined with scanning electron microscopy (SEM), and local surface conductivity measurements of the electrode surfaces were done with atomic force microscopy (AFM). Particle size distribution on the electrode surface was investigated and single PTFE particles in the catalyst layer were resolved. A great influence of the PTFE content in the electrodes on the performance of membrane electrode assemblies (MEA) was observed in single cell experiments. Reducing the PTFE content resulted in a decrease of the internal resistance of the MEA and improvement of the phosphoric acid uptake and its distribution in the cell. Both properties helped enhance the fuel cell performance.<br